Progress in diagnosing and treating thyroid squamous cell carcinoma under the 5th edition of WHO classification - Ding, Wei; Gao, Xiaofan; Ran, Xuan (Frontiers in Endocrinology, 2024)
Squamous cell carcinoma of the thyroid (SCCT) is a rare thyroid gland malignancy, with only a few hundred cases reported in the literature, mostly as case reports or small sample studies. In the previous WHO classification, squamous cell carcinoma of the thyroid was defined as a carcinoma composed entirely of squamous cells without differentiated carcinoma components. It was once included in the WHO tumor classification separately. However, the 2022 WHO classification of squamous cell carcinoma of the thyroid was reclassified as a morphologic subtype of anaplastic thyroid carcinoma (ATC). The squamous cell carcinoma pattern is similar to the other histologic types of ATC, but the phenotype associated has a poorer prognosis. The typical clinical manifestation of this condition is a cervical mass, accompanied by indications and symptoms of compression on adjacent structures such as the esophagus and trachea in advanced stages. Secondary squamous cell carcinoma of the thyroid may occur due to the spread of squamous carcinoma of the larynx or esophagus or distant metastases from other sites. Diagnosis of squamous cell carcinoma of the thyroid includes neck Ultrasound (US), Computed Tomography (CT) or Magnetic Resonance Imaging (MRI), puncture tissue biopsy, and full endoscopy to identify metastatic lesions from the nasopharynx, oropharynx, hypopharynx, larynx, esophagus, or bronchi and to help with the initial staging of the tumor. Current treatment modalities include surgery, radiotherapy, chemotherapy, or a combination. Because of the poor prognosis of patients with this disease, the short survival period, usually less than one year, and the difficulty of preoperative diagnosis, this article reviews the epidemiological features, origin, clinical features, pathological features, and differential diagnosis to improve the diagnosis and treatment of this disease by clinicians.